2020
DOI: 10.1051/e3sconf/202021016001
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Strategies of Social Media Discourse

Abstract: We have attempted to analyse the features of communicative strategies of a media discourse. The paper describes the notions of “discourse”, “media discourse”, “social media discourse”, and “communicative strategies”. The research is performed using the social media texts collected by the authors. Up to date no linguistic investigations of communicative strategies used in social media discourse have been conducted. We have focused on news texts from information, news, educational, and entertaining platforms, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The strategies of meaning transferring highlighted in our study are in some respects consistent with the list of communicative strategies presented by various authors: for example, the "Evaluation" strategy existing in our classification is highlighted in the work (Klemenova and Ereshchenko, 2020). P. B.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The strategies of meaning transferring highlighted in our study are in some respects consistent with the list of communicative strategies presented by various authors: for example, the "Evaluation" strategy existing in our classification is highlighted in the work (Klemenova and Ereshchenko, 2020). P. B.…”
Section: Discussionsupporting
confidence: 89%
“…I. S. Luchinkina revealed that the user's communicative behavior depends on the type of a cognitive distortion (Luchinkina, 2018). E. Klemenova (Klemenova and Ereshchenko, 2020), studying the discourse of the social networks users, identified communicative strategies. At the same time, the authors argue that among the strategies, one can distinguish evaluation and forecasting strategies that have an impact on other users.…”
Section: Introductionmentioning
confidence: 99%
“…This multidimensional topic needs for more indepth and complete study; this problem is being still insufficiently addressed in the scientific literature. There are separate publications that focus on media literacy, the future educator's personality shaping in modern media space, and the communicative strategies of social media discourse [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…An important factor enabling achievement of the target communication goals is adequate assurance of the information exchange between the target audience and the organization, development and implementation of an information policy, and preparation and public distribution of information materials [14][15].…”
Section: Introductionmentioning
confidence: 99%